Chemical and fresh state properties of foamed concrete incorporating palm oil fuel ash and eggshell ash as cement replacement - Kamaruddin, Sufian; Wan, Inn Goh; Ahmed Jhatial, Ashfaque; Tahir Lakhiar, Muhammad (Science Publishing Corporation, 2018)
Malaysia faces three major environmental problems, out of which solid waste and management is one of them. Palm Oil Fuel Ash (POFA) and eggshells are two agro-food waste materials which are produced in enormous quantities in Malaysia. Due to the characteristics possessed by eggshells and POFA, these waste materials can potentially be utilized in the production as cement replacement, reducing the use of cement which is one of the major production of Carbon Dioxide (CO2) gas emissions. This study was conducted to determine the chemical and fresh state properties of foamed concrete incorporating POFA and eggshell ash (ESA) as cement replacement. Based upon the results, it was observed that the increase in usage amount of POFA and ESA as cement replacement, the workability of foamed concrete reduced without blocking. For the chemical analysis result shows the POFA which had high amount of silicon dioxide and ESA having large amount of calcium oxide were compatible and could be used together as cement replacement. The use of ESA and POFA as cement replacement to reduce the cement consumption with various percentage of ESA (0% - 15%) and POFA (20% - 35%) in 1800 kg/m3 density of foamed concrete